2022
DOI: 10.1167/iovs.63.6.24
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary Muscle Dimension Changes With Accommodation Vary in Myopia and Emmetropia

Abstract: Purpose The purpose of this study was to determine whether accommodation-induced changes in ciliary muscle dimensions vary between emmetropes and myopes, and the effect of the image analysis method. Methods Seventy adults aged 18 to 27 years consisted of 25 people with emmetropia (spherical equivalent refraction [SER] +0.21 ± 0.36 diopters [D]) and 45 people with myopia (−2.84 ± 1.72 D). There were 23 people with low myopia (>−3 D) and 22 people with moderate myopia (−3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(65 reference statements)
2
13
0
Order By: Relevance
“…They found that during the process of accommodation, there was a pronounced thickening of the anterior muscle and a shortening of the curved nasal muscle length, notably more so in myopic eyes than in emmetropic ones. For consistent measurements within the same subject, they advocate the use of a fixed distance approach, while recommending a proportional distance methodology for cross-group refractive comparisons [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that during the process of accommodation, there was a pronounced thickening of the anterior muscle and a shortening of the curved nasal muscle length, notably more so in myopic eyes than in emmetropic ones. For consistent measurements within the same subject, they advocate the use of a fixed distance approach, while recommending a proportional distance methodology for cross-group refractive comparisons [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another area of interest resides in the anatomy and biomechanics of the ciliary body, which governs lens shape. Specifically, myopic individuals exhibit a larger and stiffer ciliary muscle, potentially impacting accommodative function [ 14 ]. The concept of peripheral defocus, characterized by hyperopic defocus in the outer retinal regions, has emerged as a possible contributing element in myopia development [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a larger project where emmetropes and myopes underwent a series of tests over a few days. The following measurements were taken for both unaccommodated and accommodated states: autorefraction, aberrometry, 13 ciliary muscle dimensions, 14 peripheral choroidal thickness and peripheral eye length. Screening to check suitability was completed for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Speci cally, myopic individuals exhibit a larger and stiffer ciliary muscle, potentially impacting accommodative function. 12 The concept of peripheral defocus, characterized by hyperopic defocus in the outer retinal regions, has emerged as a possible contributing element in myopia development. 13 Nevertheless, the role of peripheral defocus as either a cause or consequence of myopia remains an ongoing debate.…”
Section: Introductionmentioning
confidence: 99%